PENETAPAN KADAR VITAMIN C PADA EKSTRAK DAUN PEPAYA (Carica papaya L.) MUDA DAN TUA DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Aptika Oktaviana Trisna Dewi; Niken Wahyu Nur Hidayah; Adnan Nur Aviv (Jurnal Farmasindo, 2020)
Papaya is the one of Indonesian plant which has a lot of health benefits. The part of the plant that often used is the leaves. The one of papaya’s leaves benefit is used as antioxidant for various diseases. The substance that use as antioxidant is vitamin C. This observation is order to find out the level of vitamin C in papaya’s young and old leaves extract by UV-Vis spectrophotometry. The determination of vitamin C level was done by quantitative and qualitative tests of papaya’s leaves extract that obtained by infusion. Qualitative tests was conducted by flavonoid test and alkaloid test with color reagent. While the quantitative test is determined based on the absorbance value using UV-Vis spechtrophotometry that measured at wavelength of 265 nm with comparison of ascorbic acid. The result was obtained that papaya’s leaves extract are contained flavonoids and alkaloids with an average level of vitamin C in young papaya’s leaves in amount of 0.299%, compare with old papaya’s leaves in amount of 0,421%. Statistical test result shows the assymp sign value is 0,00 < 0,05, it indicates that the age of the leaves influences the significance of vitamin C level on papaya leaves.